2019
DOI: 10.1111/coa.13324
|View full text |Cite
|
Sign up to set email alerts
|

Vocal nodules management

Abstract: Vocal fold nodules present the voice clinic team with a number of clinical dilemmas which are not as simple as previously thought. The definition, aetiology, prevalence and diagnosis are all poorly understood. Furthermore, treatment evidence for both behavioural and surgical approaches is weak. This paper reviews the published evidence pertaining to all of these aspects. Specific areas of uncertainty that remain include: poorly defined nomenclature, the natural history of paediatric vocal nodules, the establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Vocal nodules were the most frequent laryngeal lesions (n = 78), corroborating the findings of other authors [8,[17][18][19]. In our study, surgical indications for vocal nodules were restricted to 12 cases (15.38%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Vocal nodules were the most frequent laryngeal lesions (n = 78), corroborating the findings of other authors [8,[17][18][19]. In our study, surgical indications for vocal nodules were restricted to 12 cases (15.38%).…”
Section: Discussionsupporting
confidence: 92%
“…According to Birchall and Carding [19] there is no level of evidence I for vocal nodule treatment. The authors emphasize that the most recent systematic reviews include only nonrandomized interventional studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the sample shows female dominance, constituting 95.2% of the participants. The literature is unanimous in mentioning a higher incidence of vocal disorders in women [25]. Smith et al (1996) at the University of Iowa and Utah showed a 2/1 woman-to-man ratio in vocal disorder treatments [26].…”
Section: Discussionmentioning
confidence: 99%
“…There is no Level 1 evidence as to which method is effective for treating patients with VFN ( 4 ). A Cochrane review reported evidence from non‐randomized interventional studies (Levels 2‐4) only ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…A Cochrane review reported evidence from non‐randomized interventional studies (Levels 2‐4) only ( 5 ). In daily clinical practice, most clinicians prefer voice therapy (VT) as the primary method ( 2 , 4 ). The evidence base for the effectiveness of VT is constantly evolving ( 4 , 6 ).…”
Section: Introductionmentioning
confidence: 99%